2019
DOI: 10.22435/jbmi.v8i1.2585
|View full text |Cite
|
Sign up to set email alerts
|

Korelasi Kontrol Glikemik dengan HDL dan Small-Dense LDL pada Penderita Diabetes Melitus dengan Komplikasi Jantung Koroner di RSUP Dr. Kariadi Semarang, Jawa Tengah

Abstract: Abstract Blood glucose level could be measured before 2-3 months using glycated haemoglobin (HbA1c). In diabetes mellitus (DM) the size of low-density lipoprotein (LDL-K) often changes to a small size, called small dense LDL-K sdLDL) which is atherogenic and low high-density lipoprotein (HDL) level. High HbA1c indicates uncontrolled glucose levels and often cause complications of coronary heart disease (CHD). This is a further investigation from the previous one about ”The Relationship between HbA1c with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(3 reference statements)
1
3
1
Order By: Relevance
“…In addition, the generic risk factors of DM are hypertension and increased creatinine level. Our finding of an association between hypertension and creatinine level showed consistency with the previous study [12,27] a significant association between sdLDL-C, hypertension, and creatinine level. Table 3 shows mean systolic, diastolic, and creatinine levels across quintiles.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the generic risk factors of DM are hypertension and increased creatinine level. Our finding of an association between hypertension and creatinine level showed consistency with the previous study [12,27] a significant association between sdLDL-C, hypertension, and creatinine level. Table 3 shows mean systolic, diastolic, and creatinine levels across quintiles.…”
Section: Discussionsupporting
confidence: 93%
“…This average was slightly lower than the results of another study in the Kerala District of India state which found average levels -HbA1c average of 8.87 ± 1.8% (Najeeb et al, 2022). Research at the Kariadi Hospital in Semarang found an average HbA1c of 8.72 ± 1.73 (Driyah, BS, & DK, 2019). HbA1c is the glycated component of hemoglobin.…”
Section: Discussioncontrasting
confidence: 61%
“…The findings of this study are higher than the findings of other studies. Research at the Kariadi Hospital in Semarang found an average LDL of 110.64 ± 32.10 (Driyah et al, 2019). In said study, it was also found that most (83.87%) had uncontrolled LDL levels, LDL is a group of low-density lipoproteins of various sizes.…”
Section: Discussionmentioning
confidence: 72%

Glycemic Control Determinant of Diabetes Mellitus Patients

I Wayan Sukawana,
I Made Sukarja,
Listina Ade Widya Ningtyas
et al. 2023
NHSJ
“…This finding is supported by research from Driyah et al (2019), who say glycemic control has a significant relationship with HDL levels. His research also says that high medication adherence can achieve controlled glycemic levels.…”
Section: Resultsmentioning
confidence: 54%